EFFECTS OF NASAL IRRIGATION SOLUTIONS ON HUMAN SINONASAL CILIARY BEAT FREQUENCY: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2026)
Objectives: This scoping review aims to synthesize current evidence regarding the effects of different saline-based solutions on human sinonasal ciliary beat frequency.Methods: A literature review was conducted across PubMed, Google Scholar, and Semantic Scholar databases. Studies published in English focusing on the interaction between nasal irrigation constituents and human sinonasal ciliary motility were included for qualitative analysis.Results: 10 studies meeting the eligibility criteria were analyzed, all utilizing ciliary beat frequency as the primary outcome measure. The findings indicate that ciliary beat frequency is significantly modulated by both tonicity and ionic composition. Hypotonic and the majority of isotonic solutions (4/6 studies) demonstrated no significant inhibitory effects on ciliary beat frequency. Conversely, hypertonic solutions (≥ 3.0%) exhibited divergent results, suppressing ciliary beat frequency in vitro while enhancing it exvivo. Electrolyte presence proved critical: solutions enriched with Ca2+, K+, or Cu2+/Mn2+ supplements maintained or stimulated ciliary beat frequency, whereas Ca2+ deficiency led to marked ciliary depression. Furthermore, intracellular Cl- accumulation or  depletion significantly inhibited ciliary motility, reducing activity to 0.91 of the baseline value.Conclusion: An optimal nasal irrigation solution should achieve a balance between mechanical clearance and the preservation of ciliary physiology. Clinical preference should be given to isotonic formulations enriched with essential minerals (Ca2+, K+ Cu2+, Mn2+) and  buffered systems with low Cl- content to maximize mucociliary function.
Keywords: Nasal irrigation, ciliary beat frequency, sinonasal mucosa, human.